Effect of sex on some composition traits of wild boar (wild pig) meat - Bodnárné Skobrák, Erika; Gundel, János; Jávor, András (Acta Agraria Debreceniensis, 2009)
The authors examined the nutrition value of the meat of shot wild boars (wild pigs) (n=66) from three wild boar enclosures with different feeding intensity and also the technological properties of the meat. Samples were taken immediately after the evisceration. Considering the storing and processing properties of game meat the samples were taken from m. serratus anterior. As for dry matter examination results, the highest values were measured in case of semi-intensively fed wild boars, then followed the data from the samples of intensively and extensively fed wild boars. The fat content from the meat samples of intensively and extensively fed wild boars proved to be lower while in case of the semi-ntensively fed wild boars it was higher. In females the dry matter content, while in males the fat content was higher. As for the protein content there were no differences in either the feeding groups or in the genders. It was only the water holding capacity of the samples from the meat of the females from semi-intensive feeding intensity wild boar enclosure that fell in between normal values.